Anthracnose Fruit Rot of Strawberry - James C. Mertely; Natalia A. Peres (EDIS)
Anthracnose fruit rot, caused by the fungus Colletotrichum acutatum, is an important disease for strawberry production worldwide. Other species of Colletotrichum, such as C. fragarie and C. gloeosporioides, are less frequently involved in fruit rot. Although fruit rot is the most important symptom caused by C. acutatum, the fungus can also attack other parts of the plant including the crown, leaves, petioles, and roots. This is document PP-207, a publication of the Plant Pathology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: March 2005.